Application of 3D Balanced Growth Theory to the Formation of Bulk Amorphous Alloys - Wu, YaQi; Zhang, Yong; Zhang, Tao (Frontiers in Materials, 2021)
Since the emergence of amorphous alloys as a kind of new material, it has attained a considerable efficiency improvement due to notable achievements in optimizing the fabrication process, forming mechanization and size of alloys. Amorphous alloys have been used in precision instruments devices with excellent magnetic, corrosion resistance, wear resistance, high strength, hardness, toughness, high electrical resistivity and electromechanical coupling properties, ect. As the hysteresis loss is lower than traditional transformer cores, which is conducive to energy saving and environmental protection. Hence, amorphous iron cores replaced traditional materials. As an anti-corrosion and wear-resistant coating, amorphous alloys also exhibit their excellent performance. The preparation process of the amorphous alloy is from the first amorphous alloy film obtained by evaporation deposition, to the high cooling rate ribbon spinning method to obtain the amorphous alloy thin strip. Then, the most widely used copper mold suction casting method is used to prepare the bulk amorphous alloy and the size of amorphous alloys is constantly increasing. However, the size of amorphous alloys has been suffering increasingly serious challenges, which has been limited by cooling rate and the thermal stability. Based on this, through new processes that eliminate the cooling rate gradient, such as: 3D additive manufacturing, ultrasonic production, and mold design, combined with the "entropy control" component design concept, combined with the theory of economics, the three-dimensional bulk amorphous alloy is proposed. The theory of balanced growth provides a new idea for the development and application of bulk amorphous alloys. This review offers a retrospection of the research efforts with respect to the amorphous alloys, and respectively provides elaborate description about the formation of amorphous alloy and the amorphous phase and the factors affecting the formation of the prediction criterion. We then pay attention to the problem about size limitation confronting the current. The three-dimensional balanced growth theory of bulk amorphous alloy was formed through using the balanced growth theory of economics flexibly. We have confidence that the bulk amorphous alloys have a bright future in the development.